Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-18T20:52:37+01:00
Vk=Vo-at
a=(Vo-Vk)/t
a=(15m/s-0m/s)/60s
a=15m/s/60s
a=1/4m/s²

S=Vot-1/2at²
S=15m/s*60s-1/2*1/4m/s²*(60s)²
S=900m-1/8m/s²*3600s²
S=900m-450m
S=450m

54km/h=15m/s
1 min = 60 s
2010-03-18T20:52:47+01:00
Vk - prędkość końcowa
Vp - prędkość początkowa
S - droga
a- przyspieszenie
t - czas


Vk = Vo - at
a = (Vo-Vk) : t
a = (15m/s - 0m/s) : 60s
a = 15m/s/60s
a = 1/4m / s²
S = Vot-1/2at²
S = 15m/s * 60s-1/2 * 1/4m/s² * (60s)²
S = 900m-1/8m/s² * 3600s²
S = 900m-450m
S = 450m

54km/h * 1000m/3600s = 15 m/s
minuta to 60 s

No i odp. sobie napiszesz ; d
2010-03-18T20:59:12+01:00
Vk - prędkość końcowa
Vp - prędkość początkowa
t - czas
s - droga
a- przyspieszenie
Vk = Vo - at
a = (Vo-Vk) : t
a = (15m/s - 0m/s) : 60s
a = 15m/s/60s
a = 1/4m / s²
S = Vot-1/2at²
S = 15m/s * 60s-1/2 * 1/4m/s² * (60s)²
S = 900m-1/8m/s² * 3600s²
S = 900m-450m
S = 450m
54km/h * 1000m/3600s = 15 m/s